PORTRAIT OF THE MEPE KASUR TRADITIONAL RITUAL IN THE KEMIREN VILLAGE COMMUNITY - Annajiatus Sholihah; I Kadek Yudiana; Mahfud (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Kemiren Village is a village with various traditions that still exist today, one of which is the Mepe Kasur traditional ritual tradition. The Mepe Kasur Traditional Ritual Tradition is a traditional ritual from Kemiren Village which is held once a year in the month of Zulhijjah or the month of Hajj. This traditional Mepe Kasur ritual is carried out by simultaneously drying red and black mattresses from the west to the east end of Kemiren Village. The red color on the mattress is a symbol of boldness and the black color is a symbol of continuity in the family. The aim of this research is to find out the history, symbolism and dynamics of the Mepe Kasur traditional ritual that occurs in the Kemiren Village community. The research method used is descriptive qualitative. Data collection techniques use interviews, observation and document study. The data analysis technique uses the theory of Miles and Huberman (2014), namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that initially drying mattresses was not carried out once a year, but rather was carried out by looking at the condition of the mattress. The drying of red and black mattresses also has stages as a traditional ritual in Kemiren Village. This research explains the symbolism in the red and black mattress and the dynamics that occur in the Mepe Kasur traditional ritual in 2014-2023.